Association of Surgical Necrotizing Enterocolitis and Its Timing with Retinopathy of Prematurity - Fundora, Jennifer B.; Binenbaum, Gil; Tomlinson, Lauren; Yu, Yinxi; Ying, Gui-shuang; Maheshwari, Akhil; Donohue, Pamela (American Journal of Perinatology, 2021)
Objective The study aimed to determine the association of surgical necrotizing enterocolitis (NEC) and its timing, with the development and timing of retinopathy of prematurity (ROP).Study Design This was a secondary data analysis of 7,483 preterm infants from the Postnatal Growth and Retinopathy of Prematurity Study. Associations between infants with surgical NEC, early-onset surgical NEC (8–28 days), and late-onset surgical NEC (over 28 days) with ROP were evaluated by using multivariable logistic regression models, controlling for birth weight, gestational age, small for gestational age status, chronic lung disease, intraventricular hemorrhage, hydrocephalus, patent ductus arteriosus, and periventricular leukomalacia.Results Three hundred fifty-six (4.8%) infants had surgical NEC, with 56% having early surgical NEC. Infants with surgical NEC had a higher risk of any ROP and severe ROP (adjusted odds ratio [OR]: 2.7; 95% CI: 1.9–3.7) and 2.5 (95% CI: 1.9–3.3), respectively; p < 0.001) compared with infants without surgical NEC. Infants with early surgical NEC were at the highest risk of developing ROP and severe ROP (adjusted OR: 3.1 [95% CI: 2.1–4.8], and 3.3 [95% CI: 2.3–4.7] respectively, p < 0.001). Infants with late surgical NEC were also at increased risk of developing ROP and severe ROP (adjusted OR: 2.1 [95% CI: 1.3–3.4], and 1.9 [95% CI: 1.3–2.8] respectively, p < 0.001) compared with infants without surgical NEC.Conclusion Infants with surgical NEC, especially early surgical NEC, are at higher risk of ROP and severe ROP.Key Points
Keywords: necrotizing enterocolitis; retinopathy of prematurity; prematurity; intestinal injury; neonate